SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL RIMPANG KUNYIT HITAM (Curcuma caesia Roxb.) ASAL LUWU UTARA DENGAN METODE DPPH - Hasan, Tahirah; Ida, Nur; Qifni, Septi Firqiana (Jurnal Riset Kefarmasian Indonesia, 2023)
The ethanol extract of black turmeric (Curcuma caesia Roxb.) contains flavonoids compounds which are thought to have antioxidant activity.The purpose of this study was to determine the class of chemical compounds and determine the IC50 value of the ethanol extract of black turmeric (Curcuma caesia Roxb.)rhizome from North Luwu using the DPPH method. The research method included extraction by maceration using 70% ethanol solvent. Phytochemical screening using specific reagents and antioxidant activity testing using the DPPH method using a visible spectrophotometer at a wavelength of 515 nm. The results of the phytochemical screening showed that the ethanol extract of black turmeric rhizome contained flavonoids, alkaloids, tannins and triterpenoids. The results of the antioxidant activity test showed that the ethanol extract of black turmeric (Curcuma caesia Roxb.) rhizome had an IC50 value of 108.8304 ± 1.24 μg/mL and ascorbic acid of 2.39 ± 0.04 μg/mL.